Dietary Supplementation with Naringin Improves Systemic Metabolic Status and Alleviates Oxidative Stress in Transition Cows via Modulating Adipose Tissue Function: A Lipid Perspective - Liuxue Li; Sarula Bai; Huiying Zhao; Jian Tan; Ying Wang; Ao Zhang; Linshu Jiang; Yuchao Zhao (MDPI AG, 2024)
Dairy cows face metabolic challenges around the time of calving, leading to a negative energy balance and various postpartum health issues. Adipose tissue is crucial for cows during this period, as it regulates energy metabolism and supports immune function. Naringin, one of the main flavonoids in citrus fruit and their byproducts, is a potent antioxidant and anti-inflammatory phytoconstituent. The study aimed to evaluate the effects of supplemental naringin on performance, systemic inflammation, oxidative status, and adipose tissue metabolic status. A total of 36 multiparous Holstein cows (from ~21 d prepartum through 35 d postpartum) were provided a basal control (CON) diet or a CON diet containing naringin (NAR) at 30 g/d per cow. Supplemental NAR increased the yield of raw milk and milk protein, without affecting dry matter intake. Cows fed NAR showed significantly lower levels (p < 0.05) of serum non-esterified fatty acid (NEFA), C-reactive protein, IL-1β, IL-6, malonaldehyde, lipopolysaccharide (LPS), aspartate aminotransferase, and alanine aminotransferase, but increased (p < 0.05) glutathione peroxidase activity relative to those fed CON. Supplemental NAR increased (p < 0.05) adipose tissue adiponectin abundance, decreased inflammatory responses, and reduced oxidative stress. Lipidomic analysis showed that cows fed NAR had lower concentrations of ceramide species (p < 0.05) in the serum and adipose tissue than did the CON-fed cows. Adipose tissue proteomics showed that proteins related to lipolysis, ceramide biosynthesis, inflammation, and heat stress were downregulated (p < 0.05), while those related to glycerophospholipid biosynthesis and the extracellular matrix were upregulated (p < 0.05). Feeding NAR to cows may reduce the accumulation of ceramide by lowering serum levels of NEFA and LPS and increasing adiponectin expression, thereby decreasing inflammation and oxidative stress in adipose tissue, ultimately improving their systemic metabolic status. Including NAR in periparturient cows' diets improves lactational performance, reduces excessive lipolysis in adipose tissue, and decreases systemic and adipose tissue inflammation and oxidative stress. Integrating lipidomic and proteomic data revealed that reduced ceramide and increased glycerophospholipids may alleviate metabolic dysregulations in adipose tissue, which in turn benefits systemic metabolic status.